2018
DOI: 10.1002/biot.201800226
|View full text |Cite
|
Sign up to set email alerts
|

Single Copy Transgene Integration in a Transcriptionally Active Site for Recombinant Protein Synthesis

Abstract: For the biomanufacturing of protein biologics, establishing stable cell lines with high transgene transcription is critical for high productivity. Modern genome engineering tools can direct transgene insertion to a specified genomic locus and can potentially become a valuable tool for cell line generation. In this study, the authors survey transgene integration sites and their transcriptional activity to identify characteristics of desirable regions. A lentivirus containing destabilized Green Fluorescent Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 57 publications
0
39
0
Order By: Relevance
“…Table 9 ). Interestingly, it has been shown before that unstable cell lines are more prone to apoptosis [11] . Accumulation of cell debris and free DNA from cell lysis can lead to formation of large clumps [43] , which connects to differentially expressed ECM regulators.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Table 9 ). Interestingly, it has been shown before that unstable cell lines are more prone to apoptosis [11] . Accumulation of cell debris and free DNA from cell lysis can lead to formation of large clumps [43] , which connects to differentially expressed ECM regulators.…”
Section: Resultsmentioning
confidence: 95%
“…Knowledge of the genomic profile around random integration sites along with the effect on the product of interest can be used to learn from the cell. Lentiviral mediated random transgene integrations were performed in single copy by O’Brien et al [11] and as multi-landing pad by Gaidukov et al in 2018 [12] . Both studies observed that the integration sites for cell lines with stable expression are located within transcriptionally active regions.…”
Section: Introductionmentioning
confidence: 99%
“…Open chromatin is required for robust expression, especially in multicellular organisms, where gene expression is more tightly controlled by epigenetics. 19 , 31 In K. phaffii , we detected accessibility peaks or expression in almost every transcriptional unit under both conditions tested ( Figures S1, S2, S5A ), making it likely that nearly all chromosomal IGRs in this organism are always in an open state. This result suggests that even IGRs with relatively low peak intensities are still accessible to recombination and expression machinery, and may explain why integration into all IGRs resulted in GFP-positive cells by flow cytometry.…”
Section: Results and Discussionmentioning
confidence: 94%
“… 18 Identifying sites for gene integration using ATAC-seq is especially appealing because it only requires knowledge of the genome sequence and annotated coding sequences; detailed functional annotations, transcription factor binding sites, or promoter annotations are useful but not necessary. Recently, ATAC-seq has been used to investigate varied performance of limited integration sites, 19 but the properties of a desirable integration site are still poorly understood. To enable construction of complex cell factories, a framework is needed that can predict optimal sites for integration of heterologous genes in almost any host using a simple, scalable, assay such as ATAC-seq.…”
mentioning
confidence: 99%
“…recombinant CHO cell lines. Transcriptomic and epigenetic profiling has demonstrated the relationship between epigenetic modifications, changes in gene expression, and the phenotypic output of CHO cell lines (Feichtinger et al, 2016;Hernandez et al, 2019;O'Brien et al, 2018). These studies have also begun to establish the functional annotation of the CHO genome, including the identity of putative regulatory elements and noncoding transcripts (Feichtinger et al, 2016;Hernandez et al, 2019).…”
mentioning
confidence: 99%